Corporate Social Responsibility and the Benefits of Employee Trust: A Cross-Disciplinary Perspective - Hansen, S. Duane; Dunford, Benjamin B.; Boss, Alan D.; Boss, R. Wayne; Angermeier, Ingo (2011)
Research on corporate social responsibility (CSR) has tended to focus on external stakeholders and outcomes, revealing little about internal effects that might also help explain CSR-firm performance linkages and the impact that corporate marketing strategies can have on internal stakeholders such as employees. The two studies (N = 1,116 and N = 2,422) presented in this article draw on theory from both corporate marketing and organizational behavior (OB) disciplines to test the general proposition that employee trust partially mediates the relationship between CSR and employee attitudinal and behavioral outcomes. Both studies provide evidence in support of these general relationships. Theoretical and practical implications of these findings are discussed in the context of CSR and corporate marketing research.
Keywords: Organizational Behavior; Ethical corporate marketing; Employee trust; Employee attitudes; Corporate Social Responsibility; Corporate marketing